2010
DOI: 10.1074/mcp.m110.001693
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Characterization of Extracellular Space Components in the Human Aorta

Abstract: The vascular extracellular matrix (ECM) is essential for the structural integrity of the vessel wall and also serves as a substrate for the binding and retention of secreted products of vascular cells as well as molecules coming from the circulation. Although proteomics has been previously applied to vascular tissues, few studies have specifically targeted the vascular ECM and its associated proteins. Thus, its detailed composition remains to be characterized. In this study, we describe a methodology for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
253
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(258 citation statements)
references
References 40 publications
3
253
1
1
Order By: Relevance
“…4). Although the binding of CFH to ECM was not of high affinity under our experimental conditions, it is likely relevant in vivo (49,50). One also has to consider that a relatively modest change in the concentration of regulators can have a decisive effect on complement activation because of the exponential characteristic of the activation steps.…”
Section: Discussionmentioning
confidence: 99%
“…4). Although the binding of CFH to ECM was not of high affinity under our experimental conditions, it is likely relevant in vivo (49,50). One also has to consider that a relatively modest change in the concentration of regulators can have a decisive effect on complement activation because of the exponential characteristic of the activation steps.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerostin is constitutively expressed in the aorta [16][17][18] and up-regulated in foci of vascular and valvular calcification. [19][20][21][22] The function of sclerostin in the vasculature is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, a previously described 3-step ECM fractionation method was adapted for use with mouse liver tissue (95)(96)(97). The ECM isolation method was performed on hepatic tissue of from and a model of ASH which does not cause significant fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, proteomic-based studies in other organs haves demonstrated that the matrisome responsds dynamically in composition after insult (95)(96)(97).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation